γ-Aminobutyric acid is involved in overlapping pathways against chilling injury by modulating glutamate decarboxylase and defense responses in papaya fruit - Khaliq, Ghulam; Ali, Sajid; Ejaz, Shaghef; Abdi, Gholamreza; Faqir, Yahya; Ma, Jiahua; Siddiqui, Mohammed Wasim; Ali, Asgar (Frontiers in Plant Science, 2023)
The effect of GABA (γ-Aminobutyric acid) treatment at two concentrations (1 or 5 mM) on papaya fruit stored at 4°C and 80-90% relative humidity for 5 weeks were investigated. The application of GABA at 5 mM apparently inhibited chilling injury, internal browning, electrolyte leakage, malondialdehyde (MDA), hydrogen peroxide (H2O2), polyphenol oxidase (PPO), phospholipase D (PLD) and lipoxygenase (LOX) activities of papaya fruit. Fruit treated with 5 mM GABA enhanced the activities of ascorbate peroxidase (APX), catalase (CAT), glutathione reductase (GR), superoxide dismutase (SOD), glutamate decarboxylase (GAD) and phenylalanine ammonia lyase (PAL). In addition, GABA treatment significantly displayed higher levels of proline, endogenous GABA accumulation, phenolic contents and total antioxidant activity than the non-treated papaya. The results suggested that GABA treatment may be a useful approach to improve chilling tolerance of papaya fruit by reducing oxidative stress and enhancing defence system.